Carbon emission trading scheme and corporate labor cost: Evidence from China - Ma, Jiejing; Xue, Mei; Ou, Longxi (Heliyon, 2024)
In the low-carbon economy era, the impacts of government environmental policies on the corporate labor force have received increasing attention. This study empirically examines the effects of the carbon emission trading scheme (ETS) on corporate labor costs using a sample of Chinese A-share listed companies in the industrial sector from 2007 to 2020. Empirical analysis shows that the ETS significantly increases corporate labor costs, and this finding is further supported by various robustness tests. Further analysis reveals that the ETS primarily affects labor costs by promoting the upgrading of the human capital structure, and the impact of the ETS on labor costs is more significant in enterprises in China's eastern region, those with higher labor intensity, and state-owned enterprises. Additionally, the effects of the ETS on corporate labor costs manifest mainly in the increase in the labor costs of ordinary employees. We contribute to the existing literature by enhancing the current understanding of the policy implications of the ETS and shedding light on the dynamics of corporate labor costs under the low-carbon economy.